HOW TO PRESERVE THE FERTILITY OF EJACULATE IN PROSTATE TUBERCULOSIS PATIENTS - E. V. Kul'chavenya; A. V. Osadchiy (Туберкулез и болезни лёгких)
In order to develop and to test the technique of restoration/preservation of fertility in prostate tuberculosis patients and to evaluate its e_ciency the open prospective comparative randomized trial was conducted which included 72 prostate tuberculosis patients. The patients were divided into 2 groups: the main group (49 patients) who had standard etiotropic treatment with sperm-protecting therapy, including selzinc plus and chorionic gonadotropic hormone and the comparison group (23 persons), who received etiotropic treatment only. Anti-tuberculosis treatment provided the negative impact on the ejaculate in prostate tuberculosis patients: two month treatment with TB drugs promoted the reduction of sperm number by 23.9% and the number pf actively moving sperms reduced by 10.6%, and the number of normal sperms reduced by 32.3%. The administration of sperm-protecting therapy increased the number of sperms by 47.8%, the actively moving forms of sperms (totally Group A and B) – by 40.5%, and the forms of normal sperms – by 41.9%.